KESESUAIAN LAHAN UNTUK TANAMAN REKLAMASI DI LAHAN PASCATAMBANG BATUBARA - Winda Aryani Prasetyo; Akhmad Rizalli Saidy; Kissinger Kissinger; Abdi Fithria (EnviroScienteae, 2023)
This study aims to analyze land suitability in reclamation and revegetation sites for sengon, trembesi, mahogany and acacia plants. Research was conducted in November 2022 at PT Adaro Indonesia Site Tanjung, South Kalimantan Province. Data collection was in the form of analysis of soil quality in the reclamation areas of Wara 1, Wara 2, Wara 3 and Wara 4 and data on land characteristics as a condition for growing sengon, acacia, trembesi and mahogany plants, then a matching method was carried out to obtain land suitability for these plant types. The results showed that the actual land suitability for sengon plants in the entire study area was incompatible with the inhibiting factors for nutrient retention and quite compatible with the inhibiting factors for water availability (S3nr.S2wa) and the potential land suitability was S2nr. Land suitability for acacia plants in all study areas found land that was not suitable for nutrient retention inhibiting factors (S3nr) and potential land suitability was S2nr. Land suitability for trembesi plants in Wara 1 and Wara 2 obtained land yields that were not in accordance with the nutrient retention inhibiting factor (S3nr) and S2nr potential land suitability, while in the Wara 3 and Wara 4 areas suitable land yields were obtained without any limiting factors. Land suitability for mahogany plants in all study areas found land that was not suitable for the limiting factor of nutrient retention and quite suitable for the limiting factor for water availability (S3nr.S2wa).